Aggression Level and its Associated Factors among High School Children in Lahore - Lubna Hameed, Hajra Sarwar, Muhammad Afzal, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Children in school age frequently engage in aggressive activities. Aggression has the greatest detrimental impact on both the child and the surroundings. Aggressive children are more likely to experience long-term behavioral issues and other emotional and social challenges. Violence that results from aggression is an issue that is getting more and more attention. Objective: To assess the level of aggression among high School Children in Lahore, Pakistan To determine the association of level of aggression among high School Children in Lahore to their socio-demographic and education factors Methodology: A cross-sectional analytical study was conducted in various high schools located in Lahore. A total of 278 participants were recruited using a simple random sampling approach. To gather data, the Buss Perry Aggression Scale was employed. This scale consisted of 29 questions, each offering five response options ranked from 1 to 5: 1= extremely uncharacteristic, 2= very much uncharacteristic, 3= somewhat characteristic, 4= very much characteristic, and 5= extremely characteristic. Written consent was obtained from each participant, and a proper introduction to the study was provided. Following data collection, the gathered information was entered and subjected to analysis using SPSS version 21. Results: Finding revealed that 55.40% participants had mild aggression, 33.45% had moderate aggression and very few 2.16% had severe aggression. Findings also revealed that gender has significant association with the level of aggression (Chi2 = 22.008a) and (P. value .000). Similarly the academic performance also has significant association with aggression (Chi2 = 7.686a) and (P. value .021). Moreover, the history of physical abuse was also found to be significantly associated with aggression levels (Chi square value. 15.449a) and p value (.000). The parents conflicts also found to be significantly associated with the aggression level among children (Chi2 = 10.464a) and (P. value .005). Furthermore, time spending in leisure activities was found to be negatively associated with the aggression levels (Chi square value. 11.078a) and p value (.004). Conclusion: In conclusion, majority of the children have mild and moderate levels of aggressions. Moreover various factors like gender, academic status, physical abuse and time spending in leisure time was found to have association with aggression level among high school children Keywords: Aggression Level, High school children, factors, association.